SUBCUBIC POWER DEPENDENCE OF 3RD-HARMONIC GENERATION FOR INPLANE, FAR-INFRARED EXCITATION OF INAS QUANTUM-WELLS - Markelz, A. G.; Asmar, N. G.; Gwinn, E. G.; Sherwin, M. S.; Nguyen, C.; Kroemer, H. (Semiconductor Science and Technology, 1994)
Large third-order, free-carrier nonlinear susceptibilities, chi(3) (to approximately 0.2 esu), and subcubic dependence of the third-harmonic power on the incident intensity, have been observed between 19 cm-1 and 23 cm-1 for InAs/AlSb quantum wells with electron sheet densities between 2.5 x 10(12) cm-2 and 8 X 10(12) cm-2. We find that the transmission of the fundamental, and the samples' DC conductivity, decrease with increasing incident intensity, indicating a large rise in the scattering rate. Using the intensity-dependent transmission to account for absorption in the sample is not sufficient to recover a cubic power law for the third-harmonic intensity. In addition, given the increased scattering rate indicated by the conductivity data, the bulk free-carrier chi(3) due to non-parabolicity should decrease dramatically with increasing fundamental intensity, contrary to our results. Thus, non-parabolicity alone cannot account for the observed third-harmonic response.
Sherwin, Mark S/Q-4762-2017 Sherwin, Mark S/0000-0002-3869-1893; Markelz, Andrea/0000-0003-0443-4319 S 8th International Conference on Hot Carriers in Semiconductors Aug 16-20, 1993 Oxford univ, oxford, england Sci & engn res council; royal soc; brit council; oxford univ 4